À mesa com um estrangeiro: a refeição como elemento organizador e identitário das comunidades lucanas a partir de Lucas 24,13-53. - Rocha Junior, Ozeias (2011)
Our research aims to determine the influence of Hellenistic meal in the customs of a Mediter-ranean Jewish community in the first century. We, then, a survey of contacts in the Jewish community in general had with the Greco-Roman both the diffusion and exchange of their values as in the spaces occupied by both cultures and their symbolic conceptions. Thus, we studied the influence of Greek meal in the writings of Luke and Acts. First, in exegetical reading of Luke 24.13-53, the disciples on the way to Emmaus, we see evidence that this narrative, especially in the scene of the table, the meal was marked by the inclusion of a foreigner. In a way, the constitution of the Lucan community points, especially regarding the meal for the formation of their identity. Then we find in the writings of Luke-Acts the conse-quences of contact. The material of Luke, both the Gospel and the Acts of the Apostles, presents narratives that focus on table therefore found that the act of Jesus was at table with unqualified persons, according to Jewish customs and the prospect of this material Lucan, shows the influence of Greek meal in the practice of Jewish followers of Jesus and that this practice was assimilated by this community in the early years of its formation.